THE EFFECT OF FINANCIAL LITERACY ON THE PERFORMANCE OF MICRO, SMALL, AND MEDIUM BUSINESSES IN METRO LAMPUNG CITY - Irpan Nurhab (Jurnal Ilmiah Raflesia Akuntansi, 2021)
Micro, Small, and Medium Enterprises help many people in reducing poverty. Increased financial literacy and financial inclusion can develop Micro, Small, and Medium Enterprises because Micro, Small, and Medium Enterprises actors can understand the basic concepts of financial products, good financial planning, and management, and protect them in the future from fraud and fraudulent work. not healthy. on financial markets. This study aims to determine the effect of financial literacy on the development of the performance of Micro, Small, and Medium Enterprises in Metro Lampung City. The type of research used is a quantitative approach. Collecting data from the study was based on interviews and distributing questionnaires with a sampling technique, namely simple random sampling. The number of samples used was 100 Micro, Small, and Medium Enterprises. The data analysis technique in this study was multiple linear regression analysis using the SPSS computer program. The results of this study can be concluded that financial literacy is a factor influencing the development of the performance of Micro, Small, and Medium Enterprises in Metro Lampung City